Human tumour clonogenicity in agar is improved by cell-free ascites. - Uitendaal, M. P. (Nature Publishing Group, 1983)
Replacement of enriched CMRL 1066 medium by cell-free ascites from tumour patients in the human tumour clonogenic assay described by Hamburger and Salmon (1977) increased plating efficiency for ovarian cancer cells by a median of 8-fold (range 0.4-1012 fold). In 40 experiments, two cases had a lower plating efficiency when cultured in cell-free ascites, 10 grew neither in standard medium nor in cell-free ascites and in two cases, growth was only observed in cell-free ascites. With standard medium, we observed 53% growth (greater than 5 colonies/dish) and 41% evaluable for chemosensitivity testing (greater than 30 colonies/dish). With cell-free ascites as culture medium, these figures were 71% and 63%, respectively. While under standard conditions the highest plating efficiency obtained was 0.25%, in 21% of the experiments done with cell-free ascites a plating efficiency higher than 1% was reached. We conclude that cell-free ascites is able to stimulate proliferation of ovarian cancer cells in agar and that the use of it extends the applicability of the clonogenic assay.